Four‐Dimensional Quantification of Kelvin‐Helmholtz Instabilities in the Polar Summer Mesosphere Using Volumetric Radar Imaging. Issue 1 (17th January 2020) - Chau, J. L.; Urco, J. M.; Avsarkisov, V.; Vierinen, J. P.; Latteck, R.; Hall, C. M.; Tsutsumi, M.
Abstract: We present and characterize in time and three spatial dimensions a Kelvin‐Helmholtz Instability (KHI) event from polar mesospheric summer echoes (PMSE) observed with the Middle Atmosphere Alomar Radar System. We use a newly developed radar imaging mode, which observed PMSE intensity and line of sight velocity with high temporal and angular resolution. The identified KHI event occurs in a narrow layer of 2.4 km thickness centered at 85 km altitude, is elongated along north‐south direction, presents separation between billows of ∼ 8 km in the east‐west direction, and its billow width is ∼ 3 km. The accompanying vertical gradients of the horizontal wind are between 35 and 45 m/s/km and vertical velocities inside the billows are ± 12 m/s. Based on the estimated Richardson ( < 0.25), horizontal Froude ( ∼ 0.8), and buoyancy Reynolds ( ∼ 2.5  ×  10 4 ) numbers, the observed event is a KHI that occurs under weak stratification and generates strong turbulence. Key Points: Four‐dimensional quantification of a clearly resolved Kelvin‐Helmholtz Instability event is observed with volumetric radar imaging The Richardson number is estimated to be much less than 0.25, using independent measurements The Froude number is estimated to be close to 1 (weak stratification) and a high buoyancy Reynolds number ∼ 25, 000 is estimated